Learning, Philosophy, and African Citizenship - Holma, Katariina; Kontinen, Tiina (Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This open access book discusses and addresses the compelling questions concerning the ideals of citizenship, the processes of learning to fulfill these ideals, and possibilities of education in fostering citizenship. Rather than advocating for one framework, the authors demonstrate the continuously contested nature of the concept of citizenship as theoretically discussed and practically experienced. The monograph combines, in an unconventional way, selected philosophical accounts and everyday experiences from certain locations in Tanzania and Uganda. It provides contributions from philosophical ideas drawing on scholars such as Chantal Mouffe, Rosi Braidotti, Theodor Adorno, and Étienne Balibar on the one hand, and the conceptions articulated by groups of inhabitants of rural and urban settings in Africa, on the other hand. Therefore, the book offers fresh readings under the lenses of citizenship and learning. Katariina Holma is Professor of Education and Head of the Research Unit at the University of Oulu, Finland. Tiina Kontinen is Associate Professor in International Development Studies at the University of Jyväskylä, Finland.